Effect of Eco Enzyme on Television Electromagnetic Radiation - Nurhamida; Anis Nismayanti; Sitti Rugayya; M. Syahrul Ulum; Kasman; Maskur (Tadulako Science and Technology Journal, 2024)
Research has been carried out on the effect of eco enzymes on television electromagnetic radiation. This research aims to determine the amount of electromagnetic radiation on live television before and after using an eco enzyme. Measurements were made of the amount of electromagnetic radiation from the television when it was off, and the television when it was on before and after using eco enzyme, using 2 types of eco enzyme (pineapple eco enzyme and organic material eco enzyme) with a volume of 1 liter (for 1 bottle) and 2 liters (for 2 bottles). The position of the eco enzyme with the surface of the bottle cover open is placed in front of the television screen at a measuring distance of 25 cm, 50 cm, 75 cm, 100 cm, 125 cm, 150 cm, 175 cm, and 200 cm. Television electromagnetic radiation in the form of the highest electric field and magnetic field when the television is on before using eco enzyme at a measuring distance of 25 cm respectively is 30 V/m and 0.22 Î¼T. After using the eco enzyme, the highest reduction in electromagnetic radiation occurred at a measurement distance of 25 cm. Treatment using 2 liters of pineapple eco enzyme can reduce television electromagnetic radiation in the form of electric fields and magnetic fields respectively, namely 6 V/m and 0.18 Î¼T. In the treatment using eco enzyme, a variety of organic materials with a volume of 2 liters can reduce television electromagnetic radiation in the form of electric fields and magnetic fields respectively, namely 7 V/m and 0.19 Î¼T.